2013
DOI: 10.1016/j.lfs.2013.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Early use of cardiac troponin-I and echocardiography imaging for prediction of myocardial infarction size in Wistar rats

Abstract: A cutoff value of 4.8ng/mL for cTnI could be used as early as 8h after MI to accurately identify infarct in this model, whereas echocardiographic images taken 48h after MI predicted the infarcted area 14days after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Twelve hours after the surgery, blood was collected for cTnI evaluation as a proxy for AMI extension [22]. After that, rats were randomly assigned into either vehicle (saline, n=10) group, NAC group (25 mg/kg/day for 28 days, n=5), DFX group (40 mg/kg/day for 7 days, n=9), or NAC plus DFX group (NAC 25 mg/kg/day for 28 days plus DFX 40 mg/kg/ day for 7 days, n=9).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve hours after the surgery, blood was collected for cTnI evaluation as a proxy for AMI extension [22]. After that, rats were randomly assigned into either vehicle (saline, n=10) group, NAC group (25 mg/kg/day for 28 days, n=5), DFX group (40 mg/kg/day for 7 days, n=9), or NAC plus DFX group (NAC 25 mg/kg/day for 28 days plus DFX 40 mg/kg/ day for 7 days, n=9).…”
Section: Treatmentmentioning
confidence: 99%
“…After that, rats were randomly assigned into either vehicle (saline, n=10) group, NAC group (25 mg/kg/day for 28 days, n=5), DFX group (40 mg/kg/day for 7 days, n=9), or NAC plus DFX group (NAC 25 mg/kg/day for 28 days plus DFX 40 mg/kg/ day for 7 days, n=9). The choice for starting the treatments 12 h after the surgery was to avoid any acute effect on cell viability and to be able in detecting AMI plasma marker cTnI with reliability, as demonstrated before [22]. All animals were followed for 28 days, and the drugs were administered by subcutaneous injection.…”
Section: Treatmentmentioning
confidence: 99%
“…29 Vietta et al reported that although cTnI levels measured 2 hours after CAL were not correlated with the SIA, those measured 8 hours after the procedure were correlated with that, but these levels could not discriminate the small, moderate or large infarct sizes from each other. 12 Additionally, it was reported in the study of Li et al that cTnI levels measured in the first four hours of CAL did not have a significant correlation with the SIA, but BNP levels had. 24 In the review of Csonka et al, it was concluded that troponin levels are not helpful in estimating the size of experimental infarction due to frequent false positive results.…”
Section: Presence Of An Infarct Area Equal To or Greater Than 20%mentioning
confidence: 94%
“…These methods are serum markers, echocardiography, magnetic resonance imaging (MRI), computed tomography, single photon emission computed tomography, and positron emission tomography. 3,7,[10][11][12] But they have disadvantages including low throughput, high costs, technical difficulties, low availability of these tests, and the need for profession and experience of performing them. 7,12 Therefore a reliable, achievable, and non-invasive alternative is highly desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation